2007
DOI: 10.1093/nar/gkm506
|View full text |Cite
|
Sign up to set email alerts
|

Binding parameters and thermodynamics of the interaction of the human cytomegalovirus DNA polymerase accessory protein, UL44, with DNA: implications for the processivity mechanism

Abstract: The mechanisms of processivity factors of herpesvirus DNA polymerases remain poorly understood. The proposed processivity factor for human cytomegalovirus DNA polymerase is a DNA-binding protein, UL44. Previous findings, including the crystal structure of UL44, have led to the hypothesis that UL44 binds DNA as a dimer via lysine residues. To understand how UL44 interacts with DNA, we used filter-binding and electrophoretic mobility shift assays and isothermal titration calorimetry (ITC) analysis of binding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 48 publications
(93 reference statements)
6
46
1
Order By: Relevance
“…We also demonstrated that pA104R has a binding site size of around 14 to 16 nt and a minimal binding length of 11 to 20 nt, similar to those reported for other viral DNA-binding proteins (22,23). The results obtained show that pA104R DNAbinding activity is stable at a wide range of temperatures (4°C to 37°C) and pH values (4 to 11), possibly to support ASFV replication in the soft tick vector (Ornithodoros spp.)…”
Section: Discussionsupporting
confidence: 86%
“…We also demonstrated that pA104R has a binding site size of around 14 to 16 nt and a minimal binding length of 11 to 20 nt, similar to those reported for other viral DNA-binding proteins (22,23). The results obtained show that pA104R DNAbinding activity is stable at a wide range of temperatures (4°C to 37°C) and pH values (4 to 11), possibly to support ASFV replication in the soft tick vector (Ornithodoros spp.)…”
Section: Discussionsupporting
confidence: 86%
“…6, lanes 3, 7, 9, and 11, respectively). It should be noted that all of the mutants with decreased binding affinity for DNA are not defective in the ability to increase the polymerase processivity, in contrast to the observations for UL42 (39,40) and UL44 (41). In particular, the C95E mutant, which is defective in dimer formation as well as in DNA binding activity, efficiently increased the polymerase processivity, strongly suggesting that the monomeric form of the BMRF1 protein interacts with the BALF5 polymerase catalytic subunit to function as a polymerase processivity factor.…”
Section: Mutations Of the Bmrf1 Protein Affect Its Ability To Increascontrasting
confidence: 59%
“…Although there is no complex structure between DNA and a virus polymerase processivity factor available thus far, site-directed mutation analyses of HSV-1 UL42 supported the proposal that protein-DNA interactions occur with the positively charged amino acid residues on the "back" face (40). The mutational analyses in EBV BMRF1 also demonstrated that substitutions of positively charged residues reduce the DNA-binding affinity (see under "Results").…”
Section: Discussionmentioning
confidence: 88%
“…It has been demonstrated elsewhere that UL84 is capable of binding DNA and RNA (6) and that UL44 binds to DNA (20,22,39). DNA-binding proteins can associate during IP due to their adjacent binding on DNA rather than due to proteinprotein interactions (18,38).…”
Section: Identification Of Proteins Immunoprecipitating With Ul44 Fromentioning
confidence: 99%